Utility of telemedicine in pediatric rheumatology during the COVID-19 pandemic - Ashley Perdue; Charles Mullett; Amna Umer; Paul Rosen (BMC, 2021)
Abstract Background During the COVID-19 pandemic, telemedicine has provided an alternative to in-person visits for patients practicing social distancing and undergoing quarantine. During this time, there has been a rapid expansion of telemedicine and its implementation in various clinical specialties and settings. In this observational study we aim to examine the utility of telemedicine in a pediatric rheumatology clinic, for 3 months during the COVID-19 pandemic. Methods A review of outpatient pediatric rheumatology telemedicine encounters were conducted from April-June 2020. Telemedicine visits (n = 75) were compared to patients seen in practice over the prior year in office-based visits (March 2019-March 2020) (n = 415). Patient characteristics, information on no-show visits, completed visits, new patient or follow-up status, and if new patients had received a visit within 2 weeks of calling to schedule an appointment were analyzed by chart review. An independent sample t-test and Chi Square statistic was used to determine statical significance between the two groups. A two-proportion z-test was used to compare visit metrics. Results The percentage of new patients utilizing telemedicine (60%) was lower and statistically significant compared to the percentage of new patient office visits (84%) the previous year (p < 0.0001). There was no change in no-show rate between groups and patient characteristics were similar. Conclusions This study demonstrates a statistically significant decrease in new patient visits during the pandemic with telemedicine-only appointments compared to in-office visits over the previous year. This suggests a possible hesitation to seek care during this time. However, there was no significant difference among patient characteristics between telemedicine visits during the pandemic and during in-office visits in the previous year. In our experience, patient visits were able to be conducted via telemedicine with a limited physical exam using caregiver's help during the pandemic. However, further studies will need to ascertain patient satisfaction and preference for telemedicine in the future.